Case Report: Chimeric Antigen Receptor T Cells Induced Late Severe Cytokine Release Syndrome - He, Jinping; Xu, Na; Zhou, Hongsheng; Zhou, Ya; Wu, Di; Zhao, Ruochong; Lin, Tong; Xu, Ju; Cao, Rui; Li, Peng; Liu, Qifa (Frontiers in Oncology, 2022)
Background Severe cytokine release syndrome (sCRS) has emerged as an adverse complication in the early period of chimeric antigen receptor T cell (CART) therapy, while whether sCRS occurs in the late period remains unknown. Here, we reported two patients with late sCRS. Case Presentation Case 1 was a 34-year-old female with refractory Philadelphia chromosome-positive B cell acute lymphoblastic leukemia. She achieved complete remission (CR) but experienced grade III CRS and hemophagocytic lymphohistiocytosis (HLH) 41 days after CD19-targeted CART (CART19) cells and CD22-targeted CART (CART22) cells infusion. Ineffective to tocilizumab and HLH-94 protocol (dexamethasone and etoposide), she died of a cerebral hemorrhage on day 55 after CART therapy. Case 2 was a 38-year-old male with IgG kappa multiple myeloma. He received autologous BCMA-targeted CART (BCMA-CART) therapy 4 months after HLA–matched sibling (sister) donor transplantation and developed grade III CRS 163 days after CART administration, characterized by fever, hypotension, and skin lesions. Effective to methylprednisolone and tocilizumab, his clinical response persisted for over 6.0 months. Conclusion Severe CRS could occur in the late period after CART therapy as re-expansion of CART cells possessed the potential risk for late sCRS.